Clustering public urban green spaces through ecosystem services potential: a typology proposal for place-based interventions - Vidal, Diogo Guedes (2022)
Public Urban Green Spaces (PUGS) are the main drivers for increasing the quality of urban environments, potentiating local resilience, promoting sustainable lifestyles, as well as improving both the health and well-being of their users. Municipal leaders are responsible for the maintenance of PUGS. However, current evidence identifies limited knowledge about urban green infrastructure governance since the lack of data about PUGS is the main obstacle to effective intervention. Set against this background, this study aimed to identify clusters of ecosystem services potential in 25 PUGS in the city of Porto, Portugal, through a validated tool application. Multivariate techniques allowed identifying predictor dimensions of ecosystem services potential: the environmental quality and facilities. Five PUGS clusters were validated: i) Environmentally Empowered and Socially Expectant Spaces, ii) Socioenvironmentally Empowered Spaces, iii) Environmentally Empowered but Socially Un-dynamic Spaces, iv) Socioenvironmentally Disempowered Spaces, and v) Socioenvironmentally Unexplored Spaces. This typology proposal brings to the discussion a possible solution for better qualifying these spaces, as it complements PUGS type with a socioeconomic and environmental characterisation. Furthermore, these results are useful in the design of place-based intervention in PUGS, contributing to the increase of ecosystem services potential and improving urban environment quality and sustainability.